Comparative Transcriptome Analysis to Identify Candidate Genes for FaRCg1 Conferring Resistance Against Colletotrichum gloeosporioides in Cultivated Strawberry (Fragaria × ananassa) - Chandra, Saket; Oh, Youngjae; Han, Hyeondae; Salinas, Natalia; Anciro, Ashlee; Whitaker, Vance M.; Chacon, Jose Guillermo; Fernandez, Gina; Lee, Seonghee (Frontiers in Genetics, 2021)
Colletotrichum crown rot (CCR) caused by Colletotrichum gloeosporioides is a serious threat to the cultivated strawberry (F.×ananassa). Our previous study reported that a major locus, FaRCg1, increases resistance. However, the genomic structure of FaRCg1 and potential candidate genes associated with the resistance remained unknown. Here, we performed comparative transcriptome analyses of resistant ‘Florida Elyana’ and susceptible ‘Strawberry Festival’ after infection and identified candidate genes potentially involved in resistance. In ‘Florida Elyana’ 6,099 genes were differentially expressed in response to C. gloeosporioides. Gene ontology analysis showed that the most up-regulated genes were functionally associated with signaling pathways of plant defense responses. Three genes in the genomic region of FaRCg1 were highly upregulated: a von Willebrand Factor A domain-containing protein, a subtilisin-like protease, and a TIFY 11A-like protein. Subgenome-specific markers developed for the candidate genes were tested with a diverse panel of 219 accessions from University of Florida and North Carolina State University breeding programs. Significant and positive associations were found between the HRM marker genotypes and CCR phenotypes. These newly developed subgenome-specific functional markers for FaRCg1 can facilitate development of resistant varieties through marker-assisted selection.